2020
DOI: 10.1177/2380084420926972
|View full text |Cite
|
Sign up to set email alerts
|

Whose Responsibility Is It Anyway? Exploring Barriers to Prevention of Oral Diseases across Europe

Abstract: Introduction: Dental caries, gum disease, and tooth loss are all preventable conditions. However, many dental care systems remain treatment oriented rather than prevention oriented. This promotes the treatment of oral diseases over preventive treatments and advice. Exploring barriers to prevention and understanding the requirements of a paradigm shift are the first steps toward delivering quality prevention-focused health care. Objectives: To qualitatively explore perceived barriers and facilitators to oral di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
33
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(36 citation statements)
references
References 32 publications
0
33
2
1
Order By: Relevance
“…16 Iranian and British dentists did not nd the practice of preventive dentistry to be reputable and nancially bene cial. 24,25 Several studies have reported that the current undergraduate dental education curriculum does not adequately prepare dentists for preventive dental care. 22,26,27 The lack of importance on evidence-based prevention strategies can adversely in uence student perception and views to the signi cance of incorporation into everyday dental practice.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…16 Iranian and British dentists did not nd the practice of preventive dentistry to be reputable and nancially bene cial. 24,25 Several studies have reported that the current undergraduate dental education curriculum does not adequately prepare dentists for preventive dental care. 22,26,27 The lack of importance on evidence-based prevention strategies can adversely in uence student perception and views to the signi cance of incorporation into everyday dental practice.…”
Section: Discussionmentioning
confidence: 99%
“…21 The consistent ndings were reported by Leggett et al in qualitative research. 25 In a study by Nagarajappa et al, the absence of dental auxiliaries to deliver preventive care was not considered a major barrier by most Indian dentists. Traditional Indian dentistry does not rely on dental auxiliaries since they are very few.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The other study explored dentists' perceived barriers and facilitators to preventing oral diseases in six European countries 19 . Trust in dentist-patient relationship has been identi ed as a key factor.…”
Section: Other To Measure Trustmentioning
confidence: 99%
“…11 Conversely, frustration from poor outcomes following OHE activity have been noted to impact on some dental professionals' satisfaction with their work, their perceptions of OHE efficacy, the motivation to provide it and it's effectiveness. 12,13,14,15 Negative outcomes may also influence dental professionals' perceptions of patients. Lack of patient interest, perceived or real, has been cited as a barrier to OHE for dental professionals.…”
Section: Introductionmentioning
confidence: 99%